2022
DOI: 10.1097/qai.0000000000003120
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seropositivity and HIV Viral Load Among Mozambican Pregnant Women

Abstract: Introduction: Prevalence estimates of SARS-CoV-2 infection in Africa are limited, particularly among pregnant women and in those living with HIV. This study assessed the seroprevalence of SARS-CoV-2 antibodies among Mozambican HIV-infected pregnant women during the first year of the pandemic, before COVID-19 vaccines were deployed in the country. Setting: The study was conducted in Manhiça district, a semirural area in southern Mozambique. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Antenatal care (ANC) clinics have been utilized in several countries in Africa to monitor SARS-CoV-2 seroprevalence in a healthy population of women accessing healthcare services. [5][6][7][8][9] In Ethiopia, SARS-CoV-2 surveillance conducted in ANC clinics between April 2020 and March 2021 first detected SARS-CoV-2 antibodies in June 2020 and peaked at 11.8% in February 2021. 10 Repeated cross-sectional serosurveys in ANC clinics in Kenya found that most women were seropositive for SARS-CoV-2 antibodies by October 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal care (ANC) clinics have been utilized in several countries in Africa to monitor SARS-CoV-2 seroprevalence in a healthy population of women accessing healthcare services. [5][6][7][8][9] In Ethiopia, SARS-CoV-2 surveillance conducted in ANC clinics between April 2020 and March 2021 first detected SARS-CoV-2 antibodies in June 2020 and peaked at 11.8% in February 2021. 10 Repeated cross-sectional serosurveys in ANC clinics in Kenya found that most women were seropositive for SARS-CoV-2 antibodies by October 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated cross-sectional surveys leveraging existing healthcare platforms can help monitor trends in seroprevalence during ongoing transmission while minimizing implementation costs associated with large-scale household surveys. Antenatal care (ANC) clinics have been utilized in several countries in Africa to monitor SARS-CoV-2 seroprevalence in a healthy population of women accessing healthcare services [5][6][7][8][9]. In Ethiopia, SARS-CoV-2 surveillance conducted in ANC clinics between April 2020 and March 2021 first detected SARS--CoV-2 antibodies in June 2020 and peaked at 11.8% in February 2021 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high HIV burden in sub-Saharan African countries [18], as well as the risks of SARS-CoV-2 infection during pregnancy, it is critical to investigate immune responses to SARS-CoV-2 infection and associated variants in WLWH. Most studies have only compared humoral responses between pregnant and non-pregnant women following SARS-CoV-2 infection or Covid-19 vaccination [13,15,[19][20][21]. However, there is a paucity of information on SARS-CoV-2 cell-mediated immune responses in PWH from low-and middle-income settings [12].…”
Section: Introductionmentioning
confidence: 99%